Non-uniform changes in different categories of precipitation intensity across China and the associated large-scale circulations - Miao, Chiyuan; Duan, Qingyun; Sun, Qiaohong; Lei, Xiaohui; Li, Hu (Environmental research letters, 2019)
This study focuses on changing trends in precipitation across mainland China during the period 1957-2014. We explore the influence of the El Niño-Southern Oscillation (ENSO), the Pacific Decadal Oscillation (PDO), and related large-scale atmospheric circulation variables on the changes in precipitation. The number of wet days showed statistically significant downward trends in North China, Jianghuai, South China, and Southwest of China, but upward trends on the Tibetan Plateau and in Northwest China. However, the number of very wet days increased in Jianghuai, South China and regions in Southwest China, and there was an increase in the spatial variability of a number of rainfall extremes over China. Because the changes in the frequency of wet days and very wet days were non-uniform, an increasing percentage of the total annual precipitation was derived from extreme events over large regions of mainland China. The ENSO and the PDO had a zonal influence on precipitation variability through the modulation of large-scale atmospheric circulation. Both the number of wet days and the frequency of extreme precipitation increased in southern Jianghuai and South China in El Niño years compared with La Niña years. A decrease (increase) in the number of wet days was observed in northern China (southeastern China) during positive PDO-phase years, which was likely a response to the large decrease in Southerly winds.